Peranan Guru Bimbingan Konseling dalam Mengatasi Siswa yang Klepto - Sri Minarni; Zaharuddin Nur (Program Studi Bimbingan dan Konseling FKIP UMSU, 2018)
This research is motivated by klepto student phenomenon. The purpose of this study is to see the role of teacher Guidance and Counseling in overcoming the students who have impaired klepto in SMA Gajah Mada Medan. The research used descriptive qualitative approach. Sampling technique in this research is Purposive Sampling. Based on the results of the study, it can be described that: The role of individual counseling services in SMA Gajah Mada Medan in klepto students run well and students have started to open to their problems, Students begin to understand the importance of counseling guidance in schools and start to feel the benefits of counseling guidance in school , With the implementation of individual counseling services students are expected to be more open to the problems. And kleptomania problems that occur in schools can be resolved well, and students who klepto can realize though not spontaneously.